The practice of leadership : - Conger, Jay A. (Jossey-Bass, 2007)
Jay Conger and Ron Riggio have assembled a long-overdue and comprehensive work on the best practices of leadership. This book makes it clear that leadership can indeed be learned, refined, and enhanced. From the frontline to the executive suite to the boardroom, for social entrepreneurs and CEOs alike, this is a terrific handbook."